2008
DOI: 10.1093/brain/awn046
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical characteristics of idiopathic infantile nystagmus with and without mutations in FRMD7

Abstract: Idiopathic infantile nystagmus (IIN) consists of involuntary oscillations of the eyes. The familial form is most commonly X-linked. We recently found mutations in a novel gene FRMD7 (Xq26.2), which provided an opportunity to investigate a genetically defined and homogeneous group of patients with nystagmus. We compared clinical features and eye movement recordings of 90 subjects with mutation in the gene (FRMD7 group) to 48 subjects without mutations but with clinical IIN (non-FRMD7 group). Fifty-eight female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 32 publications
1
63
1
7
Order By: Relevance
“…Consistently with this, we have observed the expression of FRMD7 within the developing horizontal neural integrator (nucleus prepositus and medial vestibular nuclei). 7,22 In this family, we report horizontal, vertical and torsional nystagmus associated with a PAX6 mutation. Neuroimaging in patients with PAX6 mutations have revealed abnormalities in the cerebellar grey matter.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistently with this, we have observed the expression of FRMD7 within the developing horizontal neural integrator (nucleus prepositus and medial vestibular nuclei). 7,22 In this family, we report horizontal, vertical and torsional nystagmus associated with a PAX6 mutation. Neuroimaging in patients with PAX6 mutations have revealed abnormalities in the cerebellar grey matter.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously reported a phenotypic heterogeneity associated with nystagmus in families with FRMD7 mutations and also in patients with periodic alternating nystagmus. 7,22 These data suggest that the nystagmus phenotype is not defined solely by genotype.…”
Section: Discussionmentioning
confidence: 90%
“…The discovery of FRMD7 as a "motor" nystagmus gene is fascinating and the function of this gene and protein should pave the way to better understanding of the mechanisms behind nystagmus and of treatment targets (39). Likewise, while Down syndrome has long been known to be a predisposition for nystagmus, only recently have the ocular or neurologic aberrations responsible for nystagmus in trisomy 21 patients been studied and reported (40).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previously published report. 25 The clinical significance of hemi/homozygous as compared with heterozygous mutation is not yet known, although Kaplan et al 13 found a missense mutation, R229G, in the FRMD7 gene in heterozygous and homozygous condition in members of a large X-linked NYS family without phenotypic variation. The location of the present residues is highly conserved in multiple species (Figure 1c) suggesting that the mutation at codon 305 is likely to have a significant effect on FRMD7 protein functionality.…”
Section: Resultsmentioning
confidence: 99%